The impact of age, gender and fasting blood glucose on serum lipid profile at tertiary care hospital: a retrospective study - Almaqati, Thekra; Gazwani, Ali M; Taha, Murtda; Almusabi, Saleh; Elnagi, Elmoeiz A.; Maawadh, Rawan M; Almish, Mohammed; Alqahtani, Faten Abdullah; Alnaam, Yaser (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: This relatively large retrospective study explores the impact of age, gender and fasting blood glucose level on lipid profile. It has been known that many factors could influence the lipid profile. It is crucial to investigate these relationships as dyslipidemia has been linked to many critical diseases such as cardiovascular disease. Methods:Data of 3115 individuals were collected include the age, gender, total serum cholesterol, high-density lipoprotein (HDL), low-density lipoproteins (LDL), triglyceride (TGL) and fasting glucose levels at King Fahad Military Medical Complex's Clinical Chemistry Laboratory, Dhahran, from January 2019 to July 2019. Results: The results shows that people who were 65 years or older had significant association with total cholesterol (p